Pemantauan status kesehatan dan gizi anak usia dini - A. Mushawwir Taiyeb; Muhammad Junda (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Nutrition and health are important prerequisites forthe success of early childhood education. The nutrients arebrain-forming materials and other organs related to childdevelopment, and play a role in the formation of childimmunity. Whereas health is a guarantee for the continuity ofthe early childhood education process. This activity aims toprovide counseling to early childhood education teachers onhow to monitor or check children's health in general, andanalyze the nutritional status of early childhood based onanthropometric measurements (weight and height). Themethod used was direct observational nature that is natural andpleasant. In addition, the methods used were interviews andinteractive discussions between participants and theimplementation team and between participants andparticipants. The counseling participants were kindergartenteachers who are members of the Takalar District KindergartenTeacher Association and parents of Azzahra PAUDKindergarten children. Based on the results of monitoring bythe implementing team, it was found that the participants wereable to detect children's health status by recognizing physicalsigns of healthy children, and were able to assess thenutritional status of children by measuring and analyzinganthropometric status based on body weight and height. Theparticipants were very enthusiastic about participating in thisprogram. They were very active during the discussion sessionand they also attended the event until it was completed.Furthermore, some participants asked for additional time toobtain more information about children's health and nutrition.